1990
DOI: 10.3181/00379727-193-42993
|View full text |Cite
|
Sign up to set email alerts
|

Blood Platelets and Schistosome Egg Excretion

Abstract: The eggs of helminths of the Schistosoma genus require to be extravasated in order to continue the life cycle of the parasite. The possible mode by which this takes place was investigated in a mouse model. Suppression of platelet activity in Schistosoma mansoni-infected mice by administering rabbit anti-mouse platelet serum or a selection of "antiplatelet drugs" resulted in a significant reduction of parasite egg excretion. This reduction was best achieved when antiplatelet agents were administered just before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 13 publications
(16 reference statements)
0
19
0
Order By: Relevance
“…These include the presence or absence of habitats suitable for intermediate hosts (Goll et al 1984), patterns of human activity, socioeconomic status (Lima e Costa et al 1985), densitydependent functions (Medley & Anderson 1985), and the immune response of the host (Doenhoff et al 1978, Damian 1987, Ngaiza & Doenhoff 1990, Amiri et al 1992. Recently, a relationship between genetic factors and infection intensity has been documented.…”
mentioning
confidence: 99%
“…These include the presence or absence of habitats suitable for intermediate hosts (Goll et al 1984), patterns of human activity, socioeconomic status (Lima e Costa et al 1985), densitydependent functions (Medley & Anderson 1985), and the immune response of the host (Doenhoff et al 1978, Damian 1987, Ngaiza & Doenhoff 1990, Amiri et al 1992. Recently, a relationship between genetic factors and infection intensity has been documented.…”
mentioning
confidence: 99%
“…More recently, Ngaiza and Doenhoff (1990) and Ngaiza et al (1993) have shown that, at least in some models, the anchoring of egg to endothelial cells may be mediated by platelets or their release products, since egg excretion is markedly suppressed when S. mansoni-infected mice are rendered thrombocytopenic by treatment with antiplatelet serum. Then, during the exudative stage of the periovular reaction (it is not a granuloma, but a pre-granulomatous stage), collagenase, elastase and non-specific protease production by the cell [monocytes/ macrophages, eosinophils, neutrophils and platelets (?)]…”
Section: Interaction Between Schistosomes and Re-cent Hostsmentioning
confidence: 99%
“…Schistosome egg excretion has latterly been shown to be additionally dependent on blood platelet activity [63], and on the immune response of the host [64][65][66]. The connection with tumour metastasis is clear, since both platelets and immune effector mechanisms have also from time to time been implicated in the extravasation of metastatic cells [67][68][69][70].…”
Section: Platelets and Immune Effector Mechanisms In Egg Excretionmentioning
confidence: 99%
“…mansoni eggs have a potent platelet aggregating effect both in vitro and in vivo [63]: this reaction could serve physically to lodge the eggs in the mesenteric capillaries at sites where they are laid by the female worms, and thus prevent their being swept away by the blood stream. It has recently been found that platelet release products promote the adherence of S. mansoni eggs to cultured human umbilical vein endothelial cells in vitro (Ngaiza, Doenhoff & Jaffe, in preparation), and if this occurs also in vivo it may be another factor which prevents dissipation of eggs away from the site of their initial deposition.…”
Section: Platelets and Immune Effector Mechanisms In Egg Excretionmentioning
confidence: 99%
See 1 more Smart Citation